A scoping review on associations between paratuberculosis and productivity in cattle - Griss, Silja; Knific, Tanja; Buzzell, Anne; Carmo, Luís Pedro; Schüpbach-Regula, Gertraud; Meylan, Mireille; Ocepek, Matjaž; Thomann, Beat (Frontiers in Veterinary Science, 2024)
Paratuberculosis (PTB), or Johne's disease, is a disease with worldwide distribution caused by Mycobacterium avium subsp. paratuberculosis (MAP) that leads to chronic enteritis, primarily in ruminants. Even subclinical infection significantly reduces the animals' performance, and consequences of the disease lead to high economic losses for the cattle industry. To estimate the economic burden of bovine PTB and to evaluate the benefits of a potential control program, accurate estimates of the production effects associated with the disease are required. Therefore, the aim of this scoping review was to provide a comprehensive overview of associations between MAP infection and production parameters in cattle. The studies were collected from three electronic databases. Of the total 1,605 identified studies, 1,432 did not meet the set criteria in the title and abstract screening and a further 106 were excluded during full-text review. Finally, data on 34 different production parameters were extracted from 67 publications.Results show that the magnitude of reported performance losses varies depending on several factors, such as the type of diagnostic test applied, disease status or number of lactations.Studies reported a reduction in milk yield, changes in milk quality (e.g. higher somatic cell count, lower amount of produced milk fat and protein), reduced fertility (e.g. prolonged calving interval and service period, higher abortion rate and calving difficulties), reduced weaning weight, slaughter weight and slaughter value, or a higher risk for mastitis. Results from the studies included in our review show a median decrease of milk yield per infected cow of -452 kg/lactation for raw and -405 kg/lactation for modeled data. Similarly, the amount of produced milk protein fell by a median of -14.41 kg/lactation for modeled data and the amount of produced milk fat by a median of -13.13 kg/lactation. The reviewed studies revealed a prolonged calving interval by around 30 days and a 1.5 to 3 times higher likeliness of culling per lactation in PTB positive animals.Results from this scoping review provide evidence-based inputs for the development of economic models aiming at the estimation of the costs and benefits associated with different disease control scenarios for PTB.